Avaliação da dinâmica resiliente em atletas paraibanos - Neves, Flávia Silva (2011)
Introduction: Resilience sport has very specific characteristics for being of individuals living a context of constant pressures and stress, due to the design of competitive sport as an area of high performance and selectivity. Interest in resilience in this context is necessary because the competition is configured as a confrontation and thus triggers fears and pressures on athletes, and it becomes a situation steeped in adversity. Objectives: This study aimed to examine the general dynamics of the resilient athletes who regularly participate in competitions, state of Paraíba . Method: 263 athletes took part in the following sports modalities: Taekwondo, Judo, Water Sports (swimming, diving, synchronized swimming), Handball, Basketball and Volleyball. They were catholics (67.6%), mostly male (58.9%), mostly unmarried (92%) , ages ranging from 12 to 40 years (M = 17.8, SD = 4.9), with education levels ranging from middle school to high school (76.3%), where (59.2%) had an income ranging between one thousand and five thousand. To collect the data, we used the following instruments: bio-socio-demographic questionnaire, sports pressure test , sporting Test of Fear (Roffé, 2004), RI - Resilience Inventory (Benevides-Pereira, 2008) and where they were asked two open questions: What will cause pressure on the competitive situation? How do you solve this? For the data analysis of bio-socio-demographic questionnaire , pressure tests of sport , sporting fear, and IR - Resilience Inventory outside, descriptive and multivariate statistics were used, by the means of SPSS statistical program. For the data analysis of the open questions, we used the categorical thematic content category (Figueiredo, 1993). Results: From the analysis of categorical content themes, emerged two thematic categories, 10 categories and 23 subcategories . Thematic Class I - Pressure (categories: technical aspects, results, competition, team, psychosocial, no pressure) and Thematic Class II - Coping with pressure (categories: emotional control, competitive attitudes, social support and religiosity). In relation to pressure test , the most prevalent pressure were: results pressure (M = 3.56, SD = 1.22), self- inner (M = 3.22, SD = 1.42) and pressure from the coach (M = 3.10, SD = 1.26). Related to the sporting test of fear sports, the most prevalent were: fear of injuring themselves (M = 2.90, SD = 1.45), fear of getting badly in the competition (M = 2.88, SD = 1.42), fear of not being able to give the expected (M = 2.86 , SD = 1.35), fear of not being able to turn back the result (M = 2.70, SD = 1.38) and fear of failure (M = 2.67, SD = 1.35). In all RI factors (Tenacity and Innovation-IT, Emotional Sensitivity- SE, Assertiveness-AS, Empathy-EM, Job Satisfaction- ST, and Emotional Competence-EC) were found higher mean scores showing a relatively good resilience. No significant differences were found in t test, by Student (p ≤ 0.05) on individual sports (Taekwondo, Judo, Water Sports - swimming, diving, synchronized swimming - and gymnastics) and collective (Handball, Basketball and Volleyball), but in terms of gender factors in "IT", "CE" and "SE". Also for the athletes, the result indicated that the higher the pressure for results , the higher is "IT" and "AS" . The higher the self-demands, the higher "IT" and the higher the pressure of person the higher "AS" and "IN". Regarding to the fears, the higher the "CE" minor fears of getting badly, not giving what is expected and giving back the result. Conclusion: The sport is a space that leads to adversity, but it also can promote resilience, strengthening of social support networks and multidisciplinary monitoring. Training in the management of internal and external resources is essential to promote resilience.